Potential impact of the antirheumatic agent auranofin on proviral HIV-1 DNA in individuals under intensified antiretroviral therapy: results from a randomised clinical trial - Diaz, Ricardo Sobhie; Fackler, Oliver Till; Lusic, Marina (International journal of antimicrobial agents, 2019)
Antiretroviral therapy (ART) is typically composed of a combination of three antiretroviral drugs and is the treatment of choice for people with human immunodeficiency virus type 1/acquired immune deficiency syndrome (HIV-1/AIDS). However, it is unable to impact on viral reservoirs, which harbour latent HIV-1 genomes that are able to reignite the infection upon treatment suspension. The aim of this study was to provide an estimate of the safety of the disease-modifying antirheumatic agent auranofin and its impact on the HIV-1 reservoir in humans under intensified ART. For this purpose, an interim analysis was conducted of three of the six arms of the NCT02961829 clinical trial (five patients each) with: no intervention, i.e. continuation of first-line ART; intensified ART (ART+dolutegravir and maraviroc); and intensified ART plus auranofin. Auranofin treatment was found to be well tolerated. No major adverse events were detected apart from a transient decrease in CD4+ T-cell counts at Weeks 8 and 12. Auranofin decreased total viral DNA in peripheral blood mononuclear cells compared with ART-only regimens at Week 20 (P=0.036) and induced a decrease in integrated viral DNA as quantified by Alu PCR. Despite the limited number of patient-derived sequences available in this study, phylogenetic analyses of nef sequences support the idea that auranofin may impact on the viral reservoir. [ClinicalTrials.gov ID: NCT02961829]